Analysis of the Relationship Between Project-Based Outcome and Critical Thinking Skills on the Concept of Student Computational Ability - Rahayu, Wening Patmi; Hidayat, Rachmad; Zutiasari, Ika; Rusmana, Dede; Indarwati, Rila Ayu Agnes; Zumroh, Siti (Journal of Educational Analytics, 2024)
This study aims to understand the influence of planning, project management, evaluation, cooperative thinking, and algorithmic thinking skills on the development of critical thinking ability. Using a structural equation modeling approach with path analysis, this study analyzed the relationship between these skills and critical thinking. The research method used an inferential quantitative approach by examining active students. The population is undergraduate students of Commerce Education, State University of Malang. Samples were taken from all students who fell into the population category. The results show that skills in planning, project management, and evaluation have a significant influence on critical thinking ability. The practical implications of the results of this study can be a guideline for developing student skills that are integrated with unique learning methods in higher education so that they can compete in the business world as professional workers.